2019
DOI: 10.1186/s40816-019-0100-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and evaluation of pharmacological activity of leaf Methanolic extract of Colocasia affinis Schott

Abstract: Background: The purpose of the current study is to identify the phytochemicals as well as to determine the level of antioxidant, cytotoxic, antimicrobial and in vivo analgesic, anti-inflammatory and antidiarrheal activity of leaf methanolic extract of Colocasia affinis Schott (LMCA). Methods: To appraise the antioxidant activities the extensively used total phenol, flavonoid, total antioxidant capacity, ferric reducing antioxidant power, cupric reducing antioxidant capacity and DPPH scavenging assay have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…This may be due to the organic nature of methanol and its higher capacity to dissolve organic and active bioactive compounds [45]. The results of the present study confirm the previous studies, which have reported that methanol is a better solvent for more consistent extraction of compounds from medicinal plants compared to other solvents [46,47].…”
Section: Discussionsupporting
confidence: 89%
“…This may be due to the organic nature of methanol and its higher capacity to dissolve organic and active bioactive compounds [45]. The results of the present study confirm the previous studies, which have reported that methanol is a better solvent for more consistent extraction of compounds from medicinal plants compared to other solvents [46,47].…”
Section: Discussionsupporting
confidence: 89%
“…A few recent works reported hypoglycemic, anti-allergic, and anti-inflammatory effects of CA. 13 , 14 Interestingly, a growing number of studies suggest that compounds demonstrating anti-inflammatory potentials can ameliorate diabetes and its complications. 15 In this study, we evaluated the antidiabetic effects and therapeutic efficacy of the leaves extract of CA in STZ-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Various phytochemical tests were performed for the isolated polysaccharides [23] to detect if the samples contain carbohydrates (Molisch's test), amino acids and proteins, mucilage (ruthenium red test), starch (iodine test), alkaloids (Dragendorff's test), glycosides (Keller-Killani test), tannins (ferric chloride test), and flavonoids (Shinoda test) [24].…”
Section: Phytochemical Testsmentioning
confidence: 99%